Islamic Work Behavior: Antecedent Variables and Impact on Elementary School Teacher’s Performance in Banten - Nur Afif (STAI Hubbulwathan Duri, 2022)
Education requires optimal work behaviour and performance from teachers and schools. Islamic schools that are starting to develop a lot are also required to develop the quality of education, including from the aspect of education personnel. The aims of s study were 1) to analyse the effect of motivation and job satisfaction on the performance of elementary school teachers in Banten; 2) to analyse the effect direct and indirect of job satisfaction on the work behaviour and performance of elementary school teachers in Banten as well as to analyse the effect of Islamic behaviour work on the performance of elementary school teachers in Banten. The research design was a quantitative method. The population were elementary school teachers in the Banten area. The selected sample was 105 teachers. The analysis technique was path analysis. Based on the study results, it can be concluded that motivation and job satisfaction had a positive effect on teachers' Islamic behaviour and performance in elementary school teachers in Banten. Islamic behaviour of teachers in elementary school teachers in Banten positively affected teacher performance in elementary school teachers in Banten. Motivation and job satisfaction indirectly affected elementary school teachers' performance in Banten through Islamic behaviour.